Implementasi Perkembangan Pelabuhan Hijau di Dunia Pada Pelabuhan Indonesia - Hendra Zulfikar; Dimas Rizki Saputra; Ahmad Maulana; Yohan Ananda Cahyono (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to analyze the implementation of Green port developments in the world at ports in Indonesia. The research method used is analytical descriptive with a qualitative approach. Data was collected through literature study. The results of the study show that Green ports have been implemented in various ports in the world as an effort to reduce the negative impact of port activities on the environment. The implementation of Green Ports in Indonesia is still limited and there needs to be further efforts to increase awareness and support from relevant stakeholders. In this regard, it is important for the government and the port industry in Indonesia to strengthen policies and regulations that support the implementation of green ports. In addition, there is a need for education and training for port managers and workers to increase understanding and skills in carrying out environmentally friendly practices. Overall, this research provides an overview of the implementation of Green Ports in the world and the challenges faced in implementing them in Indonesia. The implication of this research is the need for closer cooperation between the government, the port industry and the community in promoting and supporting Green Port practices to achieve sustainable development in the future.